Current indications for acute total hip arthroplasty in older patients with acetabular fracture: Evidence in 601 patients from 2002 to 2021 - Zhang, Bin-Fei; Zhuang, Yan; Liu, Lin; Xu, Ke; Wang, Hu; Wang, Bo; Wen, Hong-Quan; Xu, Peng (Frontiers in Surgery, 2023)
Purpose: Older patient population with acetabular fractures is increasing rapidly, requiring enhanced recovery. Acute total hip arthroplasty (THA) is a good option for these patients, and it is becoming increasing popular. However, acute THA has different indications in different studies. Therefore, a systematic review is needed to assess and comprehend the indications for acute THA in older patients. Methods: A systematic literature review was conducted to identify a retrospective series or prospective studies in older patients (>60 years) with acetabular fractures. The search timeline was from database construction till December 2021; PubMed, Embase, and Cochrane Library databases were searched. Two trained professional reviewers independently read the full text of documents that met the inclusion criteria and extracted information on the specific methods used and indication information based on the research design. Results: In total, there were 601 patients with acetabular fractures aged >60 years from 33 studies were obtained. Twenty-eight studies reported that THA was a feasible treatment option for acetabular fractures in geriatric patients with good outcome. The primary indications were dome impaction, irreducible articular comminution, femoral head injury, and pre-existing osteoarthritis or avascular necrosis. The most common patterns were anterior column and posterior hemitransverse, posterior wall, both columns, and T-type. Conclusion: Acute THA is an effective treatment strategy for older patients with acetabular fractures and should be considered when the abovementioned indications are observed on preoperative images. (PROSPERO: CRD42022329555)